Scriptural Tradition and the Society of Jesus in the Peregrinación de Bartolomé Lorenzo by José de Acosta - Ruiz-Leon, D; Ruiz-Leon, D (UNIV PITTSBURGH, UNIV LIBRARY SYSTEM, 2025)
The Peregrinaci & oacute;n de Bartolom & eacute; Lorenzo [1586] is a written by the Jesuit priest Jos & eacute; de Acosta whose classification has been questioned by critics regarding whether it is a novel or a biography. Without ignoring the fictional characteristics that the text presents, this paper proposes that the work corresponds to the modernization of the peregrinatio and the hagiography, both medieval writing genres. We understand this modernization as a strategy by Jos & eacute; de Acosta to place the recent Society of Jesus in the ecclesiastical tradition, at the same time as it constitutes a propaganda for the missionary process in America. by Jos & eacute; de Acosta to place the recent Society of Jesus in the ecclesiastical tradition, at the same time as it constitutes a propaganda for the missionary process in America.